Implications Of Peace Building Strategies On Peace By Catholic Justice And Peace Commission In Kwanza Sub County, Trans-Nzoia County, Kenya - Ngonela, Samuel Auchi; Mwangi, Samson Wokabi; Osamba, Joshia. O. (Advances in Social Sciences Research Journal, 2017)
Peace is inextricably linked to development. The long-term peace building activities by Catholic Justice and Peace Commission [CJPC] amid relapse into conflict has questioned the relevance of liberal peace building strategies in certain contexts. The major objective was to study the implications peace building strategies by Catholic Justice and Peace Commission [CJPC], their effects and assess are of focus in resource allocation and implementation. The Growth –with -Equity theory of peace building and Lederach’s theory of Conflict Transformation formed the theoretical framework of this study. The study adopted an exploratory case study design and both qualitative and quantitative research paradigms were employed comprising 100 households. A questionnaire, interview schedule and focus group discussions were the data collection instruments used and data was analyzed both qualitatively and quantitatively. Qualitative data collected was analyzed by use of descriptive statistics and then presented in form of Tables of frequency distribution as well as Percentages. Quantitative data used Statistical Package for Social Sciences [SPSS] and inferential statistics for analysis. Spearman ρ (rho) correlation coefficient was used to determine the nature and extent of relationship that exist between dependent and independent variables. This study findings show that there is a negative correlation between the CJPC peace building strategies and peace due to failure to observe the local context, hence lack of buy in. Bulging youth populations, contagion effect of conflict prone areas and democracy deficit are key causes of conflict apart from other underlying causes. The study recommends that success in peace building is dependent on the improvement in inter-households and inter communal relationships across boundaries, repairing relationships at a psychological level and examination of injustice and structural inequalities that sow seeds of discord for relapse to conflict. There’s need for a similar study through ethnographic research, by sharing characteristics with ‘critical’ or ‘interpretative’ research.